(untitled) (Research, Society and Development, 2022)
Skin-to-skin contact is the set of care practices related to the newborn’s first interaction with its mother. This bond must last for at least one hour, known as the “golden hour”. The practice has been widely used in recent times by health professionals, as there are several benefits, such as reduced maternal stress, ease of breastfeeding and reduced risk of infections. The objective of this article is to analyze the rates of skin-to-skin contact, in the first hour of life, in the last five years. A descriptive study of a quantitative nature was carried out through data analysis, addressing topics such as the rates of babies who were born alive or who do not need neonatal resuscitation. In addition, this study presents records of births that took place at the Hospital and Maternity Public Dona Regina Siqueira Campos, in Palmas-TO and of mothers who made skin-to-skin contact. Data related to research with puerperal women who adhered to this method in the first hour of the baby’s life were obtained. In short, the following were identified as the main factors for limiting the performance of PPC both in normal delivery and cesarean section: no notified reason, maternal impossibility, poor maternal conditions and no registration. It was evident, therefore, that practices such as mandatory training of the team, through the neonatal regulation course, advocating CPP is one of the proposed interventions, whose objective is the birth of a healthy baby, with minimal risk to the mother.